6x - 7y = 20

3x + 5y = -7

Thank you for the opportunity to help you with your question!

Define the following as Eq 1 and Eq 2:

Equation 1: 6x - 7y = 20

Equation 2: 3x + 5y = -7

Using the substitution method, solve for x in Eq 1:

x = (20 - 7y) / 6

Substitute x value in Eq 1 into Eq 2, solve for y:

3*(20 + 7y)/6 + 5y = -7

(20 + 7y)/2 + 5y = -7

20 +7y +10y = -14

17y = -34

y = -2

Plug in solved y value into Eq 1 and solve for x:

6x-7(-2)=20

6x+14=20

6x=6

x=1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up